OM-85BV na prevenção de infecções recorrentes de vias aéreas : um estudo randomizado, duplo cego, placebo controlado - Souza, Fátima Cleonice de (2017)
Introduction: Acute respiratory tract infections (ARTI) are one of the most important causes of mortality in children under 5 years old. In developed countries ARTI account for 20% of emergency consultations and 75% of antibiotic prescriptions. Children in attending day care are more prone to recurrence of respiratory infections. Bacterial immunostimulants, resulting from the chemical lysis of microorganisms associated with most respiratory tract infections, have been propagated as possibly useful intervention for prevention of recurrent respiratory infections. Objective: To analyze the effectiveness of OM-85 Broncho-vaxom (OM-85 BV) on the prevention of upper respiratory tract infections in healthy children attending preschool during the 6-month period. Methods: A randomized, double-blind, placebo controlled study was conducted in 54 healthy children aged between 6 months to 5 years attending in the School for Early Childhood Education between the months of April and September. Use of OM-85 BV for 3 months and observed for a further 3 months the following outcomes: upper respiratory tract infection, bronchopneumonia, other infections, use of antibiotics, emergency consultations, need for hospital stay, side effects of the medication. Results: Of the 54 children included, 57% were male. All completed the study and there were no significant differences between the groups. Of the 27 patients in group OM-85 BV, 19 (70,4%), attending daycare full-time and 16 (64,85%) half period, morning or evening. Breastfeeding was exclusive until 6 months in 6 patients (22,2%) on the OM-85 BV group and in 7 (25,9%) patients in the control group. Family history of smoking was positive in 11 (40,7%) patients in the OM-85 BV group and in 13 (48,1%) patients in the control group. Regarding the number of respiratory infections, the mean in the OM-85 BV group in the first 3 months was 0,92± 0,87 and in the placebo group was 0,74± 1,02 and in the 6 months was 1,62± 1,47 and 1,03±1,34, respectively. Antibiotic was used in 10 (37%) children of the OM-85BV group in the 3 months of treatment and in 13 (48,1%) of the placebo group, and in the 6 months of follow-up the use was 48,1% in both groups. The mean number of hospitalizations was very low in the period of the study. The mean number of emergency visits during the first 3 months was 0,81±1,21 in the OM-85 BV group and 1,29±1,48 in the placebo group and at 6 months was 1,77±1,80 in the OM-85 BV group and 2,03±1,76 in the placebo group. Conclusions: OM-85 BV was not effective as an intervention in daycare children with no history of IRR. No statistically significant difference was observed between the groups in the use of antibiotics, emergency consultations and hospitalizations.